Identification of an intragenic deletion in the SGCB gene through a re-evaluation of negative next generation sequencing results - Giugliano, Teresa (Neuromuscul Disord, 2016)
A large mutation screening of 504 patients with muscular dystrophy or myopathy has been performed by next generation sequencing (NGS). Among this cohort of patients, we report a case with a severe form of muscular dystrophy with a proximal weakness in the limb-girdle muscles. Her biopsy revealed typical dystrophic features and immunohistochemistry for α- and γ-sarcoglycans showed an absent reaction, addressing the clinical diagnosis toward a sarcoglycanopathy. Considering that no causative point mutation was detected in any of the four sarcoglycan genes, we re-evaluated the NGS data by careful quantitative analysis of the specific reads mapping on the four sarcoglycan genes. A complete absence of reads from the sixth exon of the β-sarcoglycan gene was found. Subsequent array comparative genomic hybridization (CGH) analysis confirmed the result with the identification of a novel 3.3 kb intragenic deletion in the SGCB gene. This case illustrates the importance of a multidisciplinary approach involving clinicians and molecular geneticists and the need for a careful re-evaluation of NGS data.